Recommendation for the review of biological reference intervals in medical laboratories - Henny,J.; Vassault,A.; Boursier,G.; Vukasovic,I.; Mesko,Brguljan P.; Lohmander,M.; Ghita,I.; Andreu,F.A.; Kroupis, C.; Sprongl,L.; Thelen,M.H.; Vanstapel,F.J.; et al. (Clin.Chem.Lab Med., 2016)
This document is based on the original recommendation of the Expert Panel on the Theory of Reference Values of the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC), updated guidelines were recently published under the auspices of the IFCC and the Clinical and Laboratory Standards Institute (CLSI). This document summarizes proposals for recommendations on: (i) The terminology, which is often confusing, noticeably concerning the terms of reference limits and decision limits. (ii) The method for the determination of reference limits according to the original procedure and the conditions, which should be used. (iii) A simple procedure allowing the medical laboratories to fulfill the requirements of the regulation and standards. The updated document proposes to verify that published reference limits are applicable to the laboratory involved. Finally, the strengths and limits of the revised recommendations (especially the selection of the reference population, the maintenance of the analytical quality, the choice of the statistical method used...) will be briefly discussed
IS - 1437-4331 (Electronic) IS - 1434-6621 (Linking) LA - eng PT - Journal Article PT - Review SB - IM
Keywords: Chemistry,Clinical; Clinical Laboratory Services; Humans; Laboratories; Reference Standards; Standards